Advances in Mechanism Design II Proceedings of the XII International Conference on the Theory of Machines and Mechanisms - Beran, Jaroslav; Bílek, Martin; Žabka, Petr.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents the most recent advances in the research of machines and mechanisms. It collects 54 reviewed papers presented at the XII International Conference on the Theory of Machines and mechanisms (TMM 2016) held in Liberec, Czech Republic, September 6-8, 2016. This volume offers an international selection of the most important new results and developments, grouped in six different parts, representing a well-balanced overview, and spanning the general theory of machines and mechanisms, through analysis and synthesis of planar and spatial mechanisms, linkages and cams, robots and manipulators, dynamics of machines and mechanisms, rotor dynamics, computational mechanics, vibration and noise in machines, optimization of mechanisms and machines, mechanisms of textile machines, mechatronics to the control and monitoring systems of machines. This conference is traditionally organised every four year under the auspices of the international organisation IFToMM and the Czech Society for Mechanics.
Preface -- Scientific Committee -- Patronage -- Part I General Theory of Machines and Mechanisms, Analysis and Synthesis of Planar and Spatial Mechanisms, Linkages and Cams, Robots and Manipulators -- IFToMM in MMS developments, by M. Ceccarelli -- General Algorithm for Computing the Theoretical Centering Precision of the Gripping Devices, by E.-C. Lovasz, V. Mesaroş-Anghel, C. M. Gruescu, C. E. Moldovan and M. Ceccarelli -- Design and Development of a Heddle Shaft Mechanism for Air-jet Weaving Machines, by F. Schwarzfischer, S. Kurtenbach, J. Onischke and B. Corves -- On Transfemoral Prosthetic Knee Design Using RRSS Motion and Axode Generation, by J. D'Alessio K. Russell and R. S. Sodhi -- On Approach Based on Lie Groups and Algebras to the Structural Synthesis of Parallel Robots, by L. Rybak, D. Malyshev and A. Chichvarin -- Life Estimation of the Contact Surfaces, by M. Hejnová and J. Ondrášek -- Calculation of the Contours of a Radial Double Cam Based on an Approximate Course of the 2nd Derivative of the Displacement Law of a Working Link, by P. Jirásko and M. Václavík -- The Elastic Compression in the Contact Region of a Cam Mechanism General Kinematic Pair, by J. Ondrášek -- Design of a Legged Walking Robot with Adjustable Parameters, by Y. Zhang, V. Arakelian and J.-P. Le Baron -- Positioning Control of a Micro Manipulation Robot Based on Voice Command Recognition for the Microscopic Cell Operation, by H. Terada, K. Makino, H. Nishizaki, E. Yanase, T. Suzuki and T. Tanzawa -- Spherical Ultrasonic Motor for Space, by U. Nishizawa, S. Toyama and T.Oohashi -- Part II Dynamics of Machines and Mechanisms, Rotor Dynamics -- Multi-Physical Analysis of the Forces in the Flexible Rotor Supported by the Magnetorheological Squeeze Film Dampers, by P. Ferfecki, J. Zapoměl and M. Marek -- Experimental Evaluation of a Rotor Model Based Foundation Identification Procedure, by M. Yu, N. Feng, E. Hahn -- Researching of the Method of Separation of Fine-Grain Particles by Centrifugationin a Liquid Medium, by A. B. Kydyrbekuly, L. A. Khajieva, G. E. Ybraev -- The Steady State Response of Multi-disc Rotors Damped by Magnetorheological Squeeze Film Dampers, by J. Zapoměl and P. Ferfecki -- Inertia Matrix and Vehicle Driveability, by P. Brabec, M. Malý and R. Voženílek -- Unexpected Vibrations of Relatively Simple Cutting Machine Mechanism, by P. Šidlof, Z. Braier, P. Klouček and J. Ondrášek -- Effect of Oil Viscosity on Pulsating Flow in Pipe, by L. Hružík, A. Bureček and M. Vašina -- Experimental Research and Mathematical Modeling of Scroll Machine in Air Motor Mode, by V.I. Ivlev, S.Yu. Misyurin and A.P. Nelyubin -- Analysis of the Mechanism of the Drill Hammer, by M. Konečný -- Free Vibration Frequency Spectrum of Four-planetary Gearing Box, by L. Půst, L. Pešek, A. Radolfová -- Speed Control of 3-phase Induction Motor in Presence of Sommerfeld Effect, by A. Bisoi, R. Bhattacharyya and A.K. Samantaray -- Part III Computational Mechanics -- Various Strategies of Elastic ForcesEvaluation in the Absolute Nodal Coordinate Formulation, by R. Bulín and M. Hajžman -- Nonlinear Vibration of Nuclear Fuel Rods, by Š. Dyk and V. Zeman -- Thermal Field Simulation of Repair Threads in a Hole in the Cover of a Pressure Vessel by Welding using Sysweld, by R. Jančo and P. Élesztős -- Simulation of Isothermal Compression Test, by I. Matoušek and O. Matoušek -- Influence of Bubbles in the Shock Liquid at its Compressibility, by M. Sivčák and T. Hruš -- Procedure for Seismic Analysis of Liquid Storage Tanks using FEM Approach and Analytical Models, by M. Sivý and M. Musil -- Part IV Vibration and Noise in Machines -- Forced Response Reduction of a Compressor Blisk Rotor Employing Intentional Mistuning, by B. Beirow, A. Kühhorn and J. Nipkau -- Flat Flexural Vibration of Drill-String with an Initial Curvature, by A.S. Sergaliyev and L.A. Khajiyeva -- A Design of the Two Architectures of Electromagnetic Vibration Energy Harvesting Devices, by M. Maták, M. Gašparík, P. Šolek, M.Margetin -- Acoustic Solution for a Car Cab Interior, by P. Němeček -- Possibilities for Reducing Car Gearbox Vibration and Noise, by E. Tomeh -- Reduced Order Analyses of Multi-Stage Coupled Structures with Main Focus on Disk-Dominated Modes, by R. Weber and A. Kühhorn -- Part V Optimization of Mechanisms and Machines, Mechanisms of Textile Machines -- Composite Production and Industrial Robot Trajectory Calculation, by T. Martinec, J. Mlýnek and M. Petrů -- The Pinion Teeth Temperatures Measured during the Different Power Levels Operation, by M. Mazac and M. Maly -- A Novel Four Wheel Vehicle, by S. Pramanik and Dr. S. S. Thipse -- Cam Mechanism for Car Seat Testing, by P. Srb, P. Kulhavy, V. Fliegel and P. Lepsik -- Offset of Natural Frequencies of Toothed Wheel by Means of Parametric Optimisation, by J.Stadnicki and M.Głąbek -- Diagnosis of a Common Rail High Pressure Injector System, by P. Starý -- Design of a Tribometer for Piston Rings, by R. Voženílek, S. Beroun and J. Břoušek -- Mathematical Model of Elastic Heald, by M. Bílek, Š. Kovář and J. Skřivánek -- Dynamic Model of the Mechanical System of the Needle Bar, by J. Komárek -- Electronic Link Between the Needle Cylinder and the Dial of the Small Diameter Knitting Machine, by J. Skřivánek, M. Bílek, O. Baťka and M. Kašpárek -- Utilization of the System of Magnetic Spring with Specific Characteristic for the Central Traversing System of the Rotor Spinning Machine, by J. Valtera -- Mechatronic Model for Traversing Rod Longitudinal Vibration Analysis, by P. Žabka -- Adaptive Timing of Relay Nozzles of an Air Jet Weaving Loom, by J. Žák -- Part VI Mechatronics, Control and Monitoring Systems of Machines -- The Testing Stand of the Direct Linear and the Torque Servo Drives Siemens Controlled by the Simotion C, by J. Antoš -- New Method of Contactless Measurement and Analysis of CNC Machine Spindle Lopping, by Z. Braier, P. Šidlof, V. Čejka and P. Žďárek -- Smart Rehabilitation Splint, by J. Cernohorsky and M. Cadek -- Implementation of Specific Displacement Diagrams for the Control of Kinetic Sculptures with Yaskawa Electronic Cams, by P. Dostrašil -- Semi-automatic Transmission in a Car, by M. Gašparík, M. Černý, P. Šolek and M. Maták -- Improvement of Dynamic Characteristics of the Car in the Light of Technological Evolution, by F. Palčák -- Rotary Table Machine Input Parameters Optimization, by A. Richter and J. Ondrášek.
Keywords: Mechanics, Applied; Control engineering; Robotics; Automation; Mechanical engineering; Mathematics -- Data processing; Engineering Mechanics; Control, Robotics, Automation; Mechanical Engineering; Computational Science and Engineering